2018
DOI: 10.1007/s11356-018-3169-6
|View full text |Cite
|
Sign up to set email alerts
|

Residues of endosulfan in cotton growing area of Vehari, Pakistan: an assessment of knowledge and awareness of pesticide use and health risks

Abstract: This study is based on self-reported information collected from selected farmers of Vehari District, Punjab, Pakistan, to determine their technical knowledge and awareness about pesticide use and associated environmental and health risks. Moreover, soil contamination by routinely used persistent organochlorine pesticide, endosulfan, was also evaluated. Survey data revealed very low literacy rate (on an average 9th grade education) and technical knowledge (almost missing) of the farmers in Vehari District. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…They found that because women are not involved in the decision making around pesticide use and work both in the fields and in the home where pesticides are stored, they are at increased risk of poisoning.’ 101 Corresponding to these findings, several studies have investigated suboptimal or a complete lack of knowledge and awareness of pesticide hazards in these regions. 102 104 Although unintentional poisoning is beyond the scope of this paper, this information is crucial in providing a glimpse of the problem and how it relates to easy accessibility and means for self-harm and suicide.…”
Section: Discussionmentioning
confidence: 99%
“…They found that because women are not involved in the decision making around pesticide use and work both in the fields and in the home where pesticides are stored, they are at increased risk of poisoning.’ 101 Corresponding to these findings, several studies have investigated suboptimal or a complete lack of knowledge and awareness of pesticide hazards in these regions. 102 104 Although unintentional poisoning is beyond the scope of this paper, this information is crucial in providing a glimpse of the problem and how it relates to easy accessibility and means for self-harm and suicide.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, existing literature highlights further hotspots. As demonstrated in several studies, toxicity effects are particularly relevant in the raw material production (e.g., due to application of pesticides in the cotton cultivation [65,66] or input of chemicals during the production of man-made fibres [67] and textile manufacturing (e.g., mainly due to the input of dyes and auxiliary materials during the textile finishing) phases. While all labels (except CmiA) have a strong focus on the textile manufacturing step, for which several restrictions and thresholds with regard to the usage of toxic substances are provided, toxicity impacts in the raw material production stage are addressed only by three labels.…”
Section: Limitations Of Resultsmentioning
confidence: 99%
“…In Pakistan, the use of pesticides has increased significantly over the past years (Tariq et al 2007). Recent studies suggest that lack of training and awareness about integrated pest management often pushes farmers toward irrational pesticide use (Ahmad et al 2019).…”
Section: Discussionmentioning
confidence: 99%